The <em><u>correct answers</u></em> are:
B=(xy + x)(xy + x)
; C=(2x – 3)(–3 + 2x)
; and E=(4y² + 25)(25 + 4y²)
Explanation:
In order to have a perfect square trinomial, we must multiply two binomials that are exactly the same. For (xy+x)(xy+x), are multiplying two identical binomials.
For (2x-3)(-3+2x), we are multiplying two binomials that are the same but written in a different order. The same is true of (4y² + 25)(25 + 4y²).
Answer:
Thank you, Also that is really cool
Step-by-step explanation:
Answer:
-1
Step-by-step explanation:
A = (0,0)
B = (1,-1)
Slope = (-1-0)/(1-0) = -1/1 = -1
Step-by-step explanation:
44 month old
12 months=1 year
44÷12=3 2/3
3 2/3 years
Answer:
yes, I can help you do it.